Sub Super Mean Labeling on a General Three Star Graph - G. Uma Maheswari; G. Margaret Joan Jebarani; V. Balaji (International Journal of Mathematics And its Applications, 2018)
In this paper, we consider a three star graph G=K_1, K_1, m K_1, n , mn with a SSML( V(4),E(2) ) , for g=[ n+-m2 ], and find the omissions and repetitions in terms of g for two different cases.